Population Structure in Chilean Hake Merluccius Gayi as Revealed by Mitochondrial Dna Sequences - Vidal-Soto, R (2012)
Genetic variation and divergence among samples of Chilean hake Merluccius gayi, from three localities off the coast of Chile and one locality off the coast of northern Peru, were assessed using sequences from the control region of mitochondrial DNA. Homogeneity tests revealed occurrence of at least three distinct genetic stocks of M. gayi within the region sampled. Factors potentially contributing to genetic divergence among M. gayi probably include hydrodynamics and behaviour. © 2012 The Authors. Journal of Fish Biology © 2012 The Fisheries Society of the British Isles.